Strategy for Enhancing the Performance Accountability of Enrekang Regency Government Agencies - Andi Waode Suastina; Nurman Sahar; Ramli Ramli (Universitas Negeri Makassar, 2022)
In recent years the level of accountability for the performance of Enrekang Regency government agencies has not shown a significant increase, so a good strategy is needed to increase it. This study uses a qualitative approach with interpretive methods and literature studies. The aim of this research is to analyze the problems in implementing government agency performance accountability and from these findings we provide strategic recommendations in improving the government agency performance accountability system in Enrekang Regency. From the research we conducted in Enrekang District, we found several components that became weaknesses in the implementation of the performance accountability system for government agencies. These components were synchronization between planning documents, result-oriented performance planning, linkages between strategic plan documents and work plans, preparation of employee performance indicators, performance measurement. employees in stages, the use of performance measurement. In improving the performance accountability system for the Enrekang Regency government agencies with strategies to increase commitment, implement performance-based budgeting, foster the importance of the Government Agency Performance Accountability System, and improve the quality of APIP in Enrekang district.